Hyperlais lutosalis (Mann, 1862) a new record to the Maltese Lepidoptera (Lepidoptera: Pyraloidea, Crambidae, Glaphyriinae) - Aldo Catania; Anthony Seguna; John J. Borg; Paul Sammut (SHILAP, 2025)
Hyperlais lutosalis (Mann, 1862) is reported for the first time from the Maltese Islands. A Maltese name is proposed for this new record.